2013
DOI: 10.1155/2013/801743
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Exercise Training on Obesity-Induced Dysregulated Expression of Adipokines in White Adipose Tissue

Abstract: Obesity is recognized as a risk factor for lifestyle-related diseases such as type 2 diabetes and cardiovascular disease. White adipose tissue (WAT) is not only a static storage site for energy; it is also a dynamic tissue that is actively involved in metabolic reactions and produces humoral factors, such as leptin and adiponectin, which are collectively referred to as adipokines. Additionally, because there is much evidence that obesity-induced inflammatory changes in WAT, which is caused by dysregulated expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 118 publications
(185 reference statements)
5
48
0
4
Order By: Relevance
“…The dose response to exercise was apparent with body fat adjustment, but we also observed a significant difference between unadjusted baseline and final levels in leptin for the high-dose exercise group. Our findings are in line with others that have investigated the effect of exercise and changes in body composition on leptin levels (32). Following 12-month aerobic exercise interventions, Abbenhardt and colleagues observed a 13% reduction in leptin levels with exercise and Frank and colleagues a 7% reduction (15,33).…”
Section: Discussionsupporting
confidence: 92%
“…The dose response to exercise was apparent with body fat adjustment, but we also observed a significant difference between unadjusted baseline and final levels in leptin for the high-dose exercise group. Our findings are in line with others that have investigated the effect of exercise and changes in body composition on leptin levels (32). Following 12-month aerobic exercise interventions, Abbenhardt and colleagues observed a 13% reduction in leptin levels with exercise and Frank and colleagues a 7% reduction (15,33).…”
Section: Discussionsupporting
confidence: 92%
“…This therefore suggests that the biological mechanisms by which exercise training provides benefits on the cardiovascular system, may underlie the protective associations demonstrated in the current study. Physical activity exerts cardioprotective effects via (i) improvement in cardiovascular risk factors such as blood pressure, biomarkers of insulin resistance, lipid and glucose levels, natriuretic peptides, and cardiac troponin T; [30][31][32] (ii) its anti-inflammatory actions, by reduction in levels of inflammatory markers such as IL-18 and C-reactive protein; [33,34] (iii) regulation of white adipose tissue mass and adipokine expression; [35] (iv) improvement in endothelial function which ultimately slows the atherosclerotic cascade; [36,37] (v) vagal control of heart rate and regulation of cardiac autonomic function; [38] and (vi) increase in cardiac output, left ventricular function, oxygen utilization, and the formation of collateral vessels. [36,39] In a meta-analysis of 160 randomized controlled trials, Lin and colleagues demonstrated that exercise significantly improved CRF with beneficial modulation of several cardiometabolic markers.…”
Section: Potential Biological Mechanismsmentioning
confidence: 99%
“…Tang [19] found that high dose NPY inhibits the proliferation of 3T3-L1 cells and promotes adipocyte differentiation. Zhang et al [20] showed that NPY promotes adipogenesis in chickens by increasing production of new preadipocytes, lipid synthesis, and lipid storage.…”
Section: Discussionmentioning
confidence: 99%